PENGEMBANGAN SENTRA BATIK SKALA HOME INDUSTRY DESA KONDANGJAJAR KABUPATEN PANGANDARAN JAWA BARAT - Agustina, Granit; Febrian, Febi; Suparyogi, Dudi (LPPM UKRI, 2025)
Batik is the work of the Indonesian people which is a blend of art and technology by the ancestors of the Indonesian nation. Indonesian batik can develop to a level that is incomparable both in design or motifs as well as in the process. Kondangjajar Village, Cijulang District, as one of the areas in Pangandaran Regency, made a breakthrough by developing the art of batik craft called